Oxidative cyclization for the synthesis of complex tetrahydrofuran-containing natural products - Pullin, R; Lipinski, R; Donohoe, T (2013)
The osmium-catalyzed oxidative cyclization of vicinal diols onto proximal olefins to generate 2,5-cis-substituted tetrahydrofurans (THFs) has been exploited as the key step for the construction of several complex THF-containing natural products, namely, the annonaceous acetogenins cis-sylvaticin, sylvaticin, and the excitatory amino acid neodysiherbaine A. Recently modified conditions that employ a Lewis acid enable the cyclization to proceed under milder conditions, providing greater tolerance to acid-sensitive functional groups, as demonstrated in two of the syntheses. Flexibility for the construction of 2,5-trans-THFs was demonstrated in the synthesis of sylvaticin by utilization of an intr-amolecular hydride-shift sequence. © 2013 IUPAC.